Strength Classification of Aras as fast-growing indigenous species timber in Sarawak - Gaddafi, Ismaili; Khairul Khuzaimah, Abdul Rahim; Alik, Duju; Iskanda, Openg; Zurina, Ismaili (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Strength properties’ tests are conducted in the form of small clear sample. This paper aimed to acquire the strength group of fast-growing indigenous species of Aras and exotic species of Acacia mangium. Thus, the information of strength properties of species is acquired from strength property's test at green and air-dry conditions. The required information namely, bending parallel to grain, compression stress parallel to grain, shear parallel to grain and modulus of elasticity. The ultimate stresses obtained from strength properties of the species is to be converted into basic and grade stresses to determine the strength group of the species based on MS 544: Part 2 (2001). The results from the study indicated that, Acacia mangium classified under strength group SG5, whilst Aras was classified under strength group SG7. The timber is classified as medium density of Light Hardwood ranging from 0.37-0.52 g/cm3 at air-dry condition.